Maternal preconception body size and early childhood growth during prenatal and postnatal periods are positively associated with child-attained body size at age 6–7 years: Results from a follow-up of the PRECONCEPT trial - Nguyen, Phuong Hong; Young, Melissa F.; Khương, Long Quỳnh; Tran, Lan Mai; Duong, Thai Hong (American Society for Nutrition, 2021)
Growth faltering is associated with adverse consequences during childhood and later life. However, questions remain on the relative importance of preconception maternal nutritional status (PMNS) and child growth during the first 1000 d of life.